The Role of Compensation and Work Environment on Loyalty of Islamic Private School Teachers - Riyadi, Slamet; WH Hasibuan, Posman; Sudadi , Sudadi; Aisyah Hanim , Siti; Faulina , Ria (Mudir : Jurnal Manajemen Pendidikan, 2023)
The goal of this study was to look at the impact of pay and school environment on teacher job loyalty at one of Islamic school in Indonesia. The study was carried out in one of Jakarta's schools, with all teachers participating. This study is a survey-correlation study. Questionnaire approaches were employed for data collection, while Path Analysis was used for analysis. The findings revealed that compensation has a direct positive effect on job loyalty; school environment has a direct positive effect on teacher job loyalty; compensation has a direct positive effect on school environment and compensation has an indirect effect on teacher job loyalty through school environment. Compensation impacts teachers' job loyalty through the mediation of a favorable school environment. The study's conclusion is that growing teacher job loyalty is decided by teacher salary. Furthermore, the conduciveness of the school environment influences the rise in teacher job loyalty. Improving remuneration will have an influence on how conducive the school atmosphere is. Meanwhile, the school environment conduciveness component mediates the influence of remuneration on employment loyalty.